Análise por componentes principais de espectros nexafs na especiação do molibdênio em catalisadores de hidrotratamento - Faro Jr,Arnaldo da C. (2010)
Bulk and supported molybdenum based catalysts, modified by nickel, phosphorous or tungsten were studied by NEXAFS spectroscopy at the Mo L III and L II edges. The techniques of principal component analysis (PCA) together with a linear combination analysis (LCA) allowed the detection and quantification of molybdenum atoms in two different coordination states in the oxide form of the catalysts, namely tetrahedral and octahedral coordination.